2014
DOI: 10.4236/ijcm.2014.514112
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Warfarin and Proton Pump Inhibitors

Abstract: Background: Interaction between proton pump inhibitors (PPI) and warfarin is controversial. Previous clinical studies have only a short follow-up period. Methods and Results: All patients (n = 716) for whom warfarin was prescribed from November 1, 2010 to October 30, 2011 were extracted from electronic health records. In retrospective analysis for 1 year, PPI were prescribed to 404 patients. Among them, 108 patients were taking warfarin for more than 6 weeks before and after PPI. The profile of these patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(25 reference statements)
0
1
0
2
Order By: Relevance
“…Связь развития геморрагических осложне-ний с приемом омепразола описана в ряде ра-бот [40][41][42]. Американской организацией по контролю за лекарственными препаратами и пищевыми продуктами (FDA) было подтвер-ждено, что прием омепразола может замедлять выведение варфарина, что приводит к повы-шению МНО и тем самым провоцирует разви-тие кровотечения.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Связь развития геморрагических осложне-ний с приемом омепразола описана в ряде ра-бот [40][41][42]. Американской организацией по контролю за лекарственными препаратами и пищевыми продуктами (FDA) было подтвер-ждено, что прием омепразола может замедлять выведение варфарина, что приводит к повы-шению МНО и тем самым провоцирует разви-тие кровотечения.…”
Section: Discussionunclassified
“…Пациенты, получающие ле-чение омепразолом и варфарином, нуждаются в тщательном мониторировании значений МНО. При этом в отличие от омепразола на-значение рабепразола не связано с развитием чрезмерной гипокоагуляции и кровотечения-ми [40,42]. В нашем исследовании подавляю-щее большинство больных, кроме двух паци-ентов, принимали омепразол, а результаты проведенного дискриминантного анализа ука-зывают на наличие достоверной связи разви-тия кровотечений с приемом омепразола.…”
Section: Discussionunclassified
“…However, while warfarin metabolism is reported to be altered by some PPIs particularly omeprazole and esomeprazole, Unge et al describe no change in coagulation time despite an increase in warfarin concentration when administered with omeprazole. Similarly, Henriksen et al reported no evidence that PPIs affected INR values in the few weeks after PPI initiation, whilst Shirayama et al reported no change in warfarin dose or INR for more than 6 weeks after addition of PPIs. In terms of bleeds, Nagata et al reported no increased risk of bleeding with PPIs, whilst two studies by Ray et al reported a reduced risk of gastrointestinal bleeds in patients taking PPIs with warfarin.…”
Section: Introductionmentioning
confidence: 99%